PENGEMBANGAN MULTIMEDIA PEMBELAJARAN BAHASA JERMAN PELAJARAN PELAYANAN RESTORAN DI YOTABAKTI YOGYAKARTA - Melly Handayani; Suwardi Endraswara (LingTera, 2015)
Tujuan penelitian dan pengembangan ini adalah (1) mengembangkan multimedia yang berisi materi dan latihan untuk keterampilan berbicara bahasa Jerman, (2) mendeskripsikan proses pengem-bangannya, dan (3) mendeskripsikan hasil evaluasi dan hasil uji coba lapangan. Uji coba terbatas dilakukan pada satu orang pengajar dan empat orang peserta didik. Uji coba lapangan melibatkan 2 orang pengajar dan 10 orang peserta didik. Data dianalisis secara deskriptif kuantitatif. Langkah pengembangan multimedia pembelajaran bahasa Jerman yang digunakan adalah (1) analisis kebutuhan, (2) perencanaan, (3) pengembangan produk, (4) evaluasi produk, (5) revisi produk, (6) uji coba lapangan, dan (7) produk akhir. Kualitas multimedia pembelajaran bahasa Jerman menurut dosen ahli materi adalah sangat baik dan menurut ahli media adalah baik. Kualitas multimedia menurut dua orang pengajar bahasa Jerman adalah sangat baik dan menurut peserta didik adalah baik. Dari 10 orang peserta didik, 80% mencapai nilai KKM. 100% respon peserta didik terhadap multimedia yang dikembangkan adalah sangat baik.Kata Kunci: Pengembangan, multimedia, keterampilan berbicara, pelayanan restoran  DEVELOPING MULTIMEDIA FOR GERMAN LANGUAGE TEACHING MATERIAL FOR RESTAURANT SERVICE LESSONS IN YOTABAKTI YOGYAKARTAAbstractThe objectives of this research and development are (1) to develop a learning media for German language teachers, a computer assisted media with learning materials and exercises for speaking skill, (2) to describe the process of developing Multimedia German Language Teaching Material for Restaurant Service Lessons, and ( 3) to describe the result of product evaluation and field try out. The small group tryout involved five participants, a German language teacher and four students of Yotabakti. Field try out involved two German language teachers and ten students. The data of this study were analysed descriptively and quantitatively. The procedures of developing multimedia German language teaching material are: (1) needs analysis, (2) planning, including instructional design and multimedia design, (3) product development, (4) evaluation of the product, including experts validation and a small group tryout, (5) revision of the product, (6) field tryout, and (7) the final product. The result of multimedia validation shows that, based on the expert at material, the material is very good and, based on the expert of media, the quality of media is good. The multimedia quality, according to two German language teachers in Yotabakti, is very good and, according to the students, it is good. 80% of 10 students in the class reached the minimum completeness criteria. The observations shows that 100% students’ responses to the developed product during the teaching and learning process is very good.Keywords: Development, multimedia, speaking skill, restaurant service lesson